Pancasila sebagai fondasi identitas nasional: memudarnya karakter kebangsaan pada generasi muda di era globalisasi - Hidayah, Syifaul Awwalina (Maliki Interdisciplinary Journal, 2026)
Indonesia’s national identity, which is based on the values of Pancasila, faces serious challenges due to the rapid flow of globalization, especially among the younger generation. The phenomenon of the fading national character is reflected in the increasing intolerance, digital individualism, weakening spirit of mutual cooperation, radicalism, moral crisis, and weak national literacy. This article aims to: (1) examine the position of Pancasila as the foundation of National Identity both philosophically and historically; (2) analyze the forms of the fading national character in the younger generation; (3) identify the causative factors in the context of globalization; and (4) formulate efforts to address the erosion of national character. The method used is library research with an approach to understand the phenomenon and analyze its causes. The data sources are accredited national journals, campus journals, and books. Analysis is conducted through content analysis and narrative synthesis. The study results show that Pancasila plays a very important role in regulating national and state life, especially in shaping a character with a national spirit. However, unfortunately, in the era of globalization, there has been a phenomenon of the fading of national character. Some of the contributing factors are globalization, digital culture, and educational institutions.